2015
DOI: 10.1021/acs.bioconjchem.5b00192
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-Free Drug-Eluting Stents: An Overview of Coating Strategies and Comparison with Polymer-Coated Drug-Eluting Stents

Abstract: Clinical evaluations have proven the efficacy of drug-elution stents (DES) in reduction of in-stent restenosis rates as compared to drug-free bare metal stents (BMS). Typically, DES are metal stents that are covered with a polymer film loaded with anti-inflammatory or antiproliferative drugs that are released in a sustained manner. However, although favorable effects of the released drugs have been observed, the polymer coating as such has been associated with several adverse clinical effects, such as late ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 79 publications
1
51
0
Order By: Relevance
“…Stents are hollow devices that are inserted in an obstructed natural passage (such as the coronary artery) to open and prevent its blockage (Chen et al, 2015;Lei et al, 2011). Since 1986, bare metal stents (BMS) have been used to treat stenosis (Puel et al, 1987;Roguin, 2011), however, one of the most common problems with these stents is neointimal proliferation (i.e., re-stenosis) (Chen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Stents are hollow devices that are inserted in an obstructed natural passage (such as the coronary artery) to open and prevent its blockage (Chen et al, 2015;Lei et al, 2011). Since 1986, bare metal stents (BMS) have been used to treat stenosis (Puel et al, 1987;Roguin, 2011), however, one of the most common problems with these stents is neointimal proliferation (i.e., re-stenosis) (Chen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that the polymeric coating of DESs leads to ST by inducing a variety of detrimental effects, including triggering the proliferation of smooth muscle cells, blocking the endothelization of nearby tissue, provoking hypersensitivity reactions, and so forth . The utilization of BP coating significantly reduced long‐term side effects of the polymer .…”
Section: Discussionmentioning
confidence: 99%
“…In general, commonly used DES can be divided into (a) polymer-coated; (b) polymer-free; (c) gene-eluting [182][183][184][185][186][187][188][189][190]; (d) nanoparticle-eluting; and (e) bioresorbable. [198,199] Biofreedom (Biosensors International)…”
Section: General Aspectsmentioning
confidence: 99%